An Analysis on English Textbook Entitled Bahasa Inggris "When English Rings a Bell" for the Eighth Year Students of Junior High School Based on the 2013 Curriculum - Arba'ati, Rani, Drs. Djoko Srijono, M.Hum, Mauly Halwat Hikmat, Ph. D (2015)
Every teacher and student need textbooks to support their teaching and learning process. A textbook is the best seen as a source in achieving aims and objectives that have already been set in terms of learners' need (Cunningsworth, 1995:7). But not all textbooks published are suitable with the learners` need and have good qualities. Thus, textbook analysis is needed to evaluate and improve a textbook which is used. This research analyzes an English textbook entitled Bahasa Inggris "When English Rings a Bell" for the eight year student of Junior High School based on the 2013 Curriculum. The aim of this study is to identify themes and materials of English textbook entitled Bahas Inggris "When English Rings a Bell" which conform to the basic competence of the 2013 Curriculum. This research uses a descriptive qualitative research. The data source of this research are English textbook entitled Bahasa Inggris "When English Rings a Bell". The writer conforms the themes and materials of English textbook entitled Bahasa Inggris "When English Rings a Bell" to the Basic Competence of the 2013 Curriculum. The writer uses document analysis as the method of collecting data. Finally, the writer concludes that not all themes and materials in every chapter in that English textbook are appropriate with the basic competences of the 2013 Curriculum. That English textbook consists of thirteen chapters and every chapter has each theme and materials. Of thirteen themes of each chapter, there are twelve chapters or 92.3 % of chapters of which the themes are appropriate with the basic competences of the 2013 Curriculum. And of thirteen chapters, there are nine chapters or 69.2 % of chapters of which the materials conform to the basic competence of the 2013 Curriculum. Keyword : English textbook, basic competence, the 2013 Curriuclum, the theme, and materials